Analyzing the differnt mobile packages and other parameters and formalization of country policy for BTRC - Rahman, Mushfiqur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.